The milieu of accountability of early companies in the Qing Dynasty: evidence from the Shànghai-based print media. - Peng, L.; Brown, Alistair (Routledge, 2015)
This study looks at evidence from the Shànghǎi (Shanghai)-based print media of the accountability of early Chinese companies from the middle period of the Qīng (Qing) Dynasty when the Opium War broke out in 1840 until the imperial monarchy's overthrow in the revolution of 1911. The Qīng Dynasty is known for its technical accounting stagnation. Yet, an examination of the Shànghǎi-based print media shows the existence of a strong sense of public reporting by early companies of the Qīng Dynasty. The findings of this study indicate that the print media displayed a rich milieu of accountability of these early companies by incorporating components of Western and Chinese benchmarks of accountability expressed in commercial metrics and key financial ratios.